Nutritional, Physicochemical, and Organoleptic Properties of Camel Meat Burger Incorporating Unpollinated Barhi Date Fruit Pulp - El Sayed, A. Abd El-Hady; Hani A. Alfheeaid; Mohamed M. Abd El-Razik; Sami A. Althwab; Hassan Barakat (International Journal of Food Science, 2022)
The chemical composition of unpollinated Barhi date fruit (UBDF) (at khalal maturity stage) pulp and its effect as fiber source or fat replacer on the quality characteristics of camel meat burgers were investigated. The UBDF was characterized by high total carbohydrate, fiber, and mineral contents. It contains substantial amounts of fiber (19.60%) and low-fat content. Prepared UBDF pulp was added to camel meat burger as a fiber source at 2.5, 5, 7.5, 10, and 15% instead of camel meat and as a fat replacer at 50, 75, and 100% instead of camel-back fat during manufacturing of camel meat burgers. Chemical composition, mineral content, instrumental color, cooking characteristics, and organoleptic properties were evaluated. Results indicated that adding UBDF as fiber source significantly reduced moisture and protein contents and increased total carbohydrates, including fiber content. In camel meat burgers, K and Ca significantly increased in UBDF level-dependent manure. Adding UBDF as a fat replacer significantly increased moisture and total carbohydrate contents, while a significant reduction in fat content has been remarked. Increasing the levels of UBDF pulp as either fiber source or fat replacer in camel burgers improved (p<0.05) shrinkage, cooking loss, and cooking yield in roasted camel burger level-dependent manure. The incorporation of UBDF pulp in camel burgers increased the lightness (L∗) values and decreased the redness (a∗) and yellowness (b∗) significantly. The formulated camel burgers with different UBDF pulp levels revealed better organoleptic characteristics than normal camel meat burgers. Interestingly, adding UBDF as fiber source at 7.5-15% presented overall acceptability of more than 90% compared to the control sample of 81.7%. In the same context, adding UBDF as a fat replacer at 100% replacing the level of added fats scored overall acceptability of more than 93.60% compared to the control sample of 67.4%. Generally, according to the results of this study, it could be concluded that UBDF pulp could be used as a functional additive to produce high-fiber and/or low-fat camel meat burgers.